Correlation of Nutritional Status with Diarrhea Incidence - Dedi Supriadi; Lia Sri Nurhayati; Reffi Nantia Khaerunnisa; Suhanda (Genius Journal, 2020)
Introduction: Diarrhea is a change of intestine movement which is marked by the increasing frequency of defecate and the liquid stool consistency. Diarrhea in lack nutrition toddler is often found in the developing country, the worse nutrition of the toddlers, the worse diarrhea happens to them. Mother's Breast milk and good nutrition enough can be the best prevention to the possibility of diarrhea. The number of toddlers who got diarrhea, the health center gave more attention because it could cause dead for the toddler. Objective: To investigate correlation between status of nutrition and incidence of diarrhea Method: this research used quantitative analytic method with cross-sectional approach. The population as many as 1,610 toddlers and the sample taken by using proportional random sampling and got collected 75 toddlers. This research was processed in univariate and bivariate and analyzed by chi square test (X2). Result: based on the toddler nutrition statue from 75 respondents, the highest frequency was less nutrition as many as 42 toddlers (56,%), the highest frequency of toddler diarrhea occurrence was 47 toddlers (62,7%), there is a significant relationship between nutrition statue and the diarrhea occurrence in toddlers because a^ p (0,05>0,000) and chi-square value of chi square (X) count > chi square (X2) table (66,237>7,815).